2019
DOI: 10.1002/epi4.12348
|View full text |Cite
|
Sign up to set email alerts
|

Possible precision medicine implications from genetic testing using combined detection of sequence and intragenic copy number variants in a large cohort with childhood epilepsy

Abstract: Objective Molecular genetic etiologies in epilepsy have become better understood in recent years, creating important opportunities for precision medicine. Building on these advances, detailed studies of the complexities and outcomes of genetic testing for epilepsy can provide useful insights that inform and refine diagnostic approaches and illuminate the potential for precision medicine in epilepsy. Methods We used a multi‐gene next‐generation sequencing (NGS) panel wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
105
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(115 citation statements)
references
References 38 publications
8
105
1
1
Order By: Relevance
“…Newer treatment options therefore should be explored. The discovery of genetic variations/mutations as the cause of epilepsy in many young children with epilepsy is a doorway to precision treatment (Ellis et al 2019, Sisodiya et al, 2019, Orsini et al, 2019, Kearney et al, 2019, Fitzgerald et al, 2019, Truty et al, 2019, Milh et al, 2016. With the advances in understanding the molecular basis of many epilepsies, targeted therapies become available, in contrast with the broad-spectrum non-specific efficacy of most existing drugs.…”
Section: Precision Medicinementioning
confidence: 99%
“…Newer treatment options therefore should be explored. The discovery of genetic variations/mutations as the cause of epilepsy in many young children with epilepsy is a doorway to precision treatment (Ellis et al 2019, Sisodiya et al, 2019, Orsini et al, 2019, Kearney et al, 2019, Fitzgerald et al, 2019, Truty et al, 2019, Milh et al, 2016. With the advances in understanding the molecular basis of many epilepsies, targeted therapies become available, in contrast with the broad-spectrum non-specific efficacy of most existing drugs.…”
Section: Precision Medicinementioning
confidence: 99%
“…Disruption of SLC6A1 is a prominent cause of neurodevelopmental disorders, including autism spectrum disorder, intellectual disability and seizures of varying types and severity. In the current three largest genomic screens of individuals with epilepsy (8565, 9170 and 9769 patients, respectively), SLC6A1 was listed among the top 10–20 genes with the highest number of pathogenic variants ( Lindy et al , 2018 ; Epi25 Collaborative, 2019 , p. 25; Truty et al., 2019 ) . In the most extensive autism sequencing study to date ( N = 11 986), SLC6A1 was among the top 10 genes, with the most significant variant enrichment in autism patients compared to 23 598 controls ( Satterstrom et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…It may also guide the identification of more genetically homogeneous subgroups within the spectrum of NDDs 3 . A recent study showed that 33% of children with a molecularly confirmed genetic epilepsy would benefit from precision medicine 4 . However, the proportion of individuals with NDDs who carry a genetic abnormality that can be identified using next‐generation sequencing (NGS) has yet to be well established.…”
Section: Introductionmentioning
confidence: 99%